"x' - y - y' = -e^t\\\\\n\n\\displaystyle\\frac{\\mathrm{d}x}{\\mathrm{d}t} - y - \\frac{\\mathrm{d}y}{\\mathrm{d}t} = -e^t\\\\\n\n\\textsf{If}\\hspace{0.1cm} y = x = e^{mt}, \\frac{\\mathrm{d}y}{\\mathrm{d}t} = \\frac{\\mathrm{d}x}{\\mathrm{d}t} = me^{mt}\\\\\n\n\\implies me^{mt} - e^{mt} - me^{mt}= -e^t\\\\\n\n-e^{mt} = -e^{t} \\implies m = 1\\\\\n\nm = 1\\hspace{0.1cm}\\textsf{is the only solution}\\\\\\textsf{to the equation.}\\\\\n\n\\therefore y = x = e^{t} \\hspace{0.1cm}\\textsf{is a solution to the first}\\\\\\textsf{order linear ODE.}"
Comments
Leave a comment